Analysis of the Limitations of the Earned Value Management Method and Evaluation of Modern Improvement Approaches in Project Management - Safari Zarch, Amir Mohammad; Mokaberian, Mohammad (Management Strategies and Engineering Sciences, 2026)
The Earned Value Management (EVM) method is one of the most comprehensive tools for monitoring and controlling projects in terms of cost and schedule performance. Despite its effectiveness in providing performance indicators and forecasting project trends, limitations such as neglecting the critical path, reliance on accurate data, and weak applicability in agile or complex project structures have led researchers to seek methods for its improvement. This article aims to critically analyze the limitations of the Earned Value Management method and examine newly proposed approaches for its enhancement. In this regard, five improved models are reviewed, including the Advanced Earned Value Model, the Agile Earned Value Management approach, integration with Value Engineering, the Weighted Earned Value Method, and the Critical-Activity-Based Model. These approaches, by focusing on enhancing the accuracy of time and cost forecasting, incorporating scope changes, weighting activities, and analytically emphasizing the project’s critical path, can effectively reduce the limitations of the traditional method. Finally, a comparative analysis among these approaches is conducted, and recommendations are provided for selecting an appropriate solution based on project type and execution conditions. The findings of this study can significantly contribute to more accurate decision-making by project managers for integrated control of time, cost, and performance.